The synthesis of fullerenes in an arc discharge - Аbdullin, Kh.А.; Gabdullin, М.Т.; Ramazanov, Т.S.; Batryshev, D.G.; Ismailov, D.V.; Schur, D.V.; Daineko, Y.A. (Recent Contributions to Physics, 2015)
In this work the methods of fullerene synthesis and purification are considered. The fullerene synthesis is carried out on a setup of arc discharge in the medium of helium gas. The purification of fullerene was carried out by well-known method – dissolution of fullerene soot in benzene with subsequent filtration and drying. Obtained samples were studied on an optical DM 6000M (Leica, Sweden) and scanning electron microscopes Ntegra Spectra. The results obtained confirm that the samples of crystals are not that different from the crystals of С60 and С70. The method of accumulation of Raman signals when the sample is constantly moving is used for quality estimation of fullerite structure, because prolonged exposure to laser radiation can lead to polymerization of fullerenes.